Plasminogen Is a Joint‐Specific Positive or Negative Determinant of Arthritis Pathogenesis in Mice. Issue 6 (June 2014) - Raghu, Harini; Jone, Alice; Cruz, Carolina; Rewerts, Cheryl L.; Frederick, Malinda D.; Thornton, Sherry; Degen, Jay L.; Flick, Matthew J.
<x xml:space="preserve">Abstract</x> Objective A fundamental metric in the diagnosis of arthropathies is the pattern of joint involvement, including differences in proximal versus distal joints and patterns of symmetric or asymmetric disease. The basis for joint selectivity among arthritides and/or within a defined disease such as rheumatoid arthritis remains enigmatic. Coagulation and fibrinolytic activity are observed in both experimental animals with inflammatory joint disease and patients with inflammatory arthritis. However, the contribution of specific hemostatic factors to joint disease is not fully defined. We sought to determine the contribution of the fibrinolytic protease, plasminogen, to tumor necrosis factor α (TNFα)–driven arthritis in distinct joints in mice. Methods The impact of plasminogen and/or fibrinogen genetic deficiencies on arthritis progression was evaluated in Tg197 mice genetically predisposed to spontaneous, nonabating, and erosive polyarthritis due to exuberant human TNFα expression. Results Elimination of plasminogen in Tg197 mice significantly exacerbated the incidence and severity of arthritis within the paw joints, but simultaneously and dramatically diminished the entire spectrum of pathologies within the knee joints of the same animals. These opposing outcomes were both mechanistically linked to fibrin(ogen), in that superimposing fibrinogen deficiency reversed both the proarthritic phenotype in the paws and arthritis resistance in the knees of plasminogen‐deficient mice. Intriguingly, the change in disease severity in the knees, but not the paws, was associated with a plasminogen‐dependent reduction in matrix metalloproteinase 9 activity. Conclusion Plasminogen is a key molecular determinant of inflammatory joint disease capable of simultaneously driving or ameliorating arthritis pathogenesis in distinct anatomic locations in the same subject.